Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.17520/biods.2018017
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the tuf gene and its upstream part genes and characteristic analysis of conserved regions and activity from related gene promoters of a phytoplasma

Abstract: Studies on the genetic diversity, key gene regulation and control of phytoplasma, which cause many diseases with various host plants and have a wide geographical distribution, will be conducive to facilitating integrated disease control. The large DNA fragments including tuf gene sequences and upstream six genes from PaWB-sdyz, PaWB-fjfz and LY-fjya1 strains were amplified using long fragment PCR primers. Sequence characteristic of conserved regions of the phytoplasma gene promoter and MLSA were performed. Ups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The results showed that the established ddPCR method was reliable for quantitative detection of AYL phytoplasma, with relatively good effect. The tuf gene is a functional protein coding gene and a relatively conserved sequence in the phytoplasma which plays an important role in protein translation and evolution of phytoplasma (Koui et al, 2003; Lai et al, 2014; Lee et al, 2000; Schneider et al, 1997; Yu et al, 2016,b, 2017, 2018). In the study, the tuf gene was used as a diagnostic assay for AYL phytoplasma for the first time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that the established ddPCR method was reliable for quantitative detection of AYL phytoplasma, with relatively good effect. The tuf gene is a functional protein coding gene and a relatively conserved sequence in the phytoplasma which plays an important role in protein translation and evolution of phytoplasma (Koui et al, 2003; Lai et al, 2014; Lee et al, 2000; Schneider et al, 1997; Yu et al, 2016,b, 2017, 2018). In the study, the tuf gene was used as a diagnostic assay for AYL phytoplasma for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…AYL1, AYL2 and AYL3 represent AYL samples; H1, H2 and H3 represent asymptomatic samples; ck1 represented TE buffer used for DNA extraction; ck2 represented ddH2O used for ddPCR reaction system. Events represented the number of droplets generated in each reaction Schneider et al, 1997;Yu et al, ,b, 2017Yu et al, , 2018. In the study, the tuf gene was used as a diagnostic assay for AYL phytoplasma for the first time.…”
Section: Detection Of Ayl Phytoplasma Targeting the Tuf Gene By Ddpcrmentioning
confidence: 99%
See 1 more Smart Citation